Verbal Formulas in the Magical Ritual: Aspects of Interaction - Tatyana A. Agapkina (Studia Litterarum)
The article traces the origins of the Eastern and Western Slavic charms intended to cast worms out of the wounds. Magical folklore of the Eastern and Western Slavs, as well as of the German peoples, counts short verbal charms recited when the wound festers and has fly larvae, or even worms, inside. Often, such charms are cast over farm animals (horses, cows, sheep, and pigs), but sometimes, though less frequently, are employed to cure people. Such Eastern and Western Slavic charms have methodological interest since they show that the symbolism of charms, their motives and language develop at the intersection of ritual, folklore imagery, and dialect speech. In the typological sense, the ritual of “breaking off” the worms can be regarded as an individual case of a broader threatening strategy in relation to plants which fits into a wider context of magical rituals.